The use of pultruded glass fiber reinforced polymer profiles in structures - Pourladian, Elias A. (Kansas State University, 2010)
Pultruded fiber reinforced polymer (FRP) shapes are gaining popularity in the construction industry. Pultruded FRP profiles introduce a new world of construction that could prove to be a viable option to traditional structural materials. The use of pultruded FRP profiles in structures is discussed in this report. First a brief history of FRPs and their applications are addressed before explaining in detail the two main components of FRP; fibers and resin. The manufacturing process known as pultrusion and how two separate materials become one structural member is examined. As a result of pultrusion, engineers and designers can create structural profiles in customizable shapes, sizes, and strengths to suit any project and price. Theoretically, a pultruded FRP profile can be customized to different strengths within the geometrical and material bounds of the profile; however, many manufacturers publish data regarding mechanical and thermal properties along with allowable loads for their nominal profiles. Currently, there are no governing codes or guidelines for pultruded FRPs but there are design manuals and handbooks published by various committees and manufacturers so the design of pultruded FRP profiles is discussed. Ultimate and serviceability limit states are design concerns that engineers always deal with but concerns of heat or fire, chemical or corrosion, and moisture affect pultruded FRPs differently than steel or wood. Pultruded FRPs pose interesting design concerns because increased customizability and workability means the member can be tailored to meet the needs for that project but that would counter the benefit of mass-produced nominal sizes. A lack of uniform codes and standards inhibits the growth of the pultrusion industry in the United States but codes developed in Europe along with the development of specialized agencies and organizations could help gain a foothold. Lastly, a set of beams varying in length and load exhibit a side-by-side comparison to examine how pultruded FRPs match up next to traditional building materials. Although wood, steel, and reinforced concrete have been the preferred materials of construction, pultruded FRP structural shapes are gaining popularity for its economical and physical advantages, and advances in manufacturing and technology stand to usher in the widespread use of pultruded FRP profiles.
Keywords: pultruded FRP beams; fiber reinforced polymers; pultrusion; fiberglass composites; Architecture (0729); Engineering, Civil (0543)